Cd uptake by Phytolacca americana L. promoted by cornstalk biochar amendments in Cd-contaminated soil. Issue 3 (23rd February 2020) - Zhang, Xinying; Zhang, Yanming; Liu, Xiaoyan; Zhang, Chenying; Dong, Shaodong; Liu, Qu; Deng, Min
Abstract: Cadmium (Cd) contamination is the most extensive pollution in China farmland. A greenhouse pot trial was conducted to investigate the effects of cornstalk biochar on Cd accumulation by Phytolacca americana L. (pokeweed) in Cd-contaminated soil. The Cd concentration increased in leaves, shoots, and roots of plants amended with 5% biochar by 79%, 113%, and 32%, respectively, compared with the pokeweed without biochar. The Cd availability, soil Cd speciation, soil fertility, root biomass, and Cd chemical forms in root were investigated to explore the mechanism by which Cd uptake increased in presence of biochar. The extractability of Cd by DTPA decreased in presence of biochar by 30% compared with that of soil without biochar. The increases occurred with dose of biochar increased in available phosphorus, labile organic carbon, and C/N atom ratio. Although, the dry weight of the aboveground part of the pokeweed decreased by 38.5%, however, the weight of roots increased by 20.8%. Root biomass and microbial activity reached maximum in the treatment that recieved 5% biochar. Cd forms extracted by NaCl and acetic acid (HAc) were predominant in root. When 5% biochar applied to soil, HAc-extracted Cd took up maximum of the increase in root.